Biochemical study of attached macroalgae from the Madeira Archipelago and beach-cast macroalgae from the Canary Islands: multivariate analysis to determine bioresource potential - Nunes, Nuno (2021)
Submitted by Paulo Borges (paulo.av.borges@uac.pt) on 2021-03-11T13:34:36Z No. of bitstreams: 1 P1612_Barreto_2020_BotanicaMarina.pdf: 2689753 bytes, checksum: 2a0de73122b4e9d3b2eef5fb2f599ad9 (MD5)